Ultrathin mesoporous graphitic carbon nitride nanosheets with functional cyano group decoration and nitrogen-vacancy defects for an efficient selective CO2 photoreduction. Issue 29 (15th July 2021) - Li, Junyi; Wang, Xiaohan; Huang, Liang; Tian, Liang; Shalom, Menny; Xiong, Chunyan; Zhang, Haijun; Jia, Quanli; Zhang, Shaowei; Liang, Feng
Abstract : Ultrathin mesoporous graphitic carbon nitride nanosheets synchronously decorated with functional cyano groups and nitrogen vacancies present excellent CO2 photoreduction performance. Abstract : Graphitic carbon nitrides have CO2 photoreduction ability, but their activities are limited by the low potential and mobility of photogenerated carriers. Herein, ultrathin mesoporous graphitic carbon nitride nanosheets (CNNS) synchronously decorated with functional cyano groups and nitrogen vacancies were prepared by a facile molten salt route. The CNNS presented unprecedentedly excellent gas-phase CO2 photoreduction performance under visible light irradiation without any co-catalyst or a sacrificial agent, and have a CH4 -yielding rate of 23.0 μmol g −1 h −1 and a selectivity of 97.9%. This boosted performance can be attributed to the synergistic effect of cyano group decoration, abundant nitrogen vacancies and extremely high surface area, which improve electron storage, charge carrier mobility, CO2 affinity, and optimize the energy band structure. This work demonstrates that a structural optimization combined with defect design of carbon nitride framework is a powerful approach to improve the photocatalytic activity, providing an accessible way to design highly efficient carbon-based photocatalysts.